THE ESCOLA SEM PARTIDO (NON-PARTISAN SCHOOL) MOVEMENT STANDPOINTS - Perez Cabral, Guilherme (Revista da Faculdade de Direito do Sul de Minas, 2019)
The article aims to discuss critically the points of view (standpoints) present in the “Escola Sem Partido (non-partisan school)” movement, from the content analysis of its draft bill, proposed by the movement, and federal bills which reproduce it. Under the perspective of the International Human Rights law, it deconstructs its legal arguments – which serve to support friend-enemy type political action, as proposed by Carl Schmitt: State neutrality; primacy of the private on the educational public and denial of the educational freedom and pluralism.